2019
DOI: 10.26452/ijrps.v10i4.1569
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel loaded transfersomal vesicular drug delivery for the treatment of melanoma skin cancers

Abstract: Over the last few years, there is tremendous growth of melanoma skin cancer in all around the world. Paclitaxel is an antineoplastic drug which is widely used for breast cancer, lung cancer, and Kaposi sarcoma. It is available only in the form of intravenous (IV), which produces tissue damage and hypersensitivity in some patients if the dose is over. In the present article, the new initiative formulation is done for melanoma skin cancer with transfersomes drug delivery systems. A different formulation of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This is due to the ability of Span-80 to entrap the drug in a small multilamellar vesicle, allowing high entrapment efficacy. Lastly, transfersomal gel was prepared by using carbopol 940 mixed with transfersome solution, and the resulting gel formed had a pH of 6.8, which could avoid the risk of irritation when applying the gel on skin surface [91]. From this study, it was proven that transfersome can entrap PTX at a high level for the treatment of melanoma skin cancer.…”
Section: Transfersomesmentioning
confidence: 92%
See 1 more Smart Citation
“…This is due to the ability of Span-80 to entrap the drug in a small multilamellar vesicle, allowing high entrapment efficacy. Lastly, transfersomal gel was prepared by using carbopol 940 mixed with transfersome solution, and the resulting gel formed had a pH of 6.8, which could avoid the risk of irritation when applying the gel on skin surface [91]. From this study, it was proven that transfersome can entrap PTX at a high level for the treatment of melanoma skin cancer.…”
Section: Transfersomesmentioning
confidence: 92%
“…Moreover, Raahulan et al studied the treatment of melanoma skin cancer by using PTX-loaded transfersomes [91]. A conventional rotary vacuum evaporator was used to prepare the transfersomes at different ratios in which the ratio of PC:Span-80 is in the range of 95-80:05-20% w/w.…”
Section: Transfersomesmentioning
confidence: 99%
“…The permeation of cytotoxic moieties in the tranferosomal system can improve skin cancer treatment. Another investigation by Sivarajakumar et al [137] prepared the paclitaxel-loaded transfersomal vesicular systems to enhance the delivery of drugs at the site of skin cancer cells by improving the permeation through the skin. The results suggested that optimized transfersomes had a flux of 6.68 ± 0.46 and a percent drug retention of (0.79 ± 0.05) through the skin of mice.…”
Section: Transferosomesmentioning
confidence: 99%
“…The results show that including the vesicles in the gel improves the ability to control release and improve skin permeation. The Carbopol-based gel was used as a vehicle for transferosomes loaded with 5-FU [141], paclitaxel [142], methotrexate [143], tofacitinib [144], tamoxifen citrate [145], and others. An interesting study was presented by Shamim et al, which includes carvedilol in transferosomes for topical administration to prevent UV-induced skin cancer [146].…”
Section: Nanovesiclesmentioning
confidence: 99%